Synthesis of (6-Methoxy-2,5-dinitro-quinoline-4-yl)-(5-vinyl-1-aza-bicyclo[2.2.2]oct-2-yl)-methanol) and In Vitro Assay Against Plasmodium falciparum 3D7 - Salahuddin Salahuddin; Rahman Emran Kartasasmita; Muhammad Hanafi; Andini Sundowo; Puspa Dewi Narrij Lotulung; Nadia Adipratiwi; Titin Ariyani; Erwahyuni Endang Prabandari; Danang Waluyo (Jurnal Kimia Valensi, 2022)
Quinine, a naturally happening alkaloid initially utilized for the treatment of muscle cramps, is currently most usually utilized to treat malaria. Symptoms of poisonous quinine, called Cinchonism, include wooziness, tinnitus (ringing in the ears), blurred vision, nausea, vomiting, serious adverse reaction to excessive quinine use, vision impairment and deafness. This research aimed to obtain more polar quinine derivatives using reactions with sulfuric acid and nitric acid to reduce toxicity. The reactions were performed analogously to the procedures reported in the literature. The characterization of reaction products utilizing proton (1H) and carbon-13 (13C) nuclear magnetic resonance (NMR) spectroscopy showed that the reaction using reagents led to nitration of the quinoline ring with the yields of 7.09 %. The IC50 value of >10.000 μg/mL was obtained from the antimalarial test against Plasmodium falciparum 3D7. The IC50 values proved that the synthesis products (6-Methoxy-2,5-dinitro-quinoline-4-yl)-(5- vinyl-1-aza-bicyclo[2.2.2]oct-2-yl)-methanol) was not potential for malaria treatment.